Bioequivalence Study of Palbociclib Capsules in Healthy Chinese Subjects Under Fasting and Fed Conditions - Chu, Nan-nan; Zhang, Lin; Wang, Jiakun; Gu, Xianghong; Ding, Ying; Huang, Kai; Que, Lin-Ling; He, Qing (Clinical drug investigation, 2022)
Background and Objective Palbociclib is an oral small-molecule inhibitor of cyclin-dependent kinase 4/6 used for the treatment of advanced breast cancer. This study compared the pharmacokinetic and safety profiles between a new generic and a branded reference formulation of palbociclib capsules in healthy Chinese subjects under fasting and fed conditions and evaluated the bioequivalence of two palbociclib products to obtain sufficient evidence for the marketing approval of the new generic drug. Methods A randomized, open-label, two-period crossover study was conducted in healthy Chinese volunteers under both fasting and fed conditions (30 subjects/condition). Eligible healthy subjects received a single 125-mg dose of the palbociclib test or reference formulation followed by a 14-day washout period. Serial blood samples were collected at scheduled timepoints, and plasma concentrations were determined by a validated high-performance liquid chromatography-tandem mass spectrometry method. A non-compartment method was used to calculate the main pharmacokinetic parameters, including the area under the plasma concentration–time curve (AUC) from time 0 to the time of the last measurable concentration (AUC 0– t ), the AUC from time 0 to infinity (AUC 0–∞ ), the maximum plasma concentration ( C max ), the time to maximum plasma concentration, and the elimination half-life. The geometric mean ratios and the corresponding 90% confidence intervals of palbociclib were acquired for the bioequivalence analysis. Safety and tolerability were assessed by monitoring adverse events, laboratory assessments, vital signs, physical examinations, and 12-lead electrocardiograms. Results Under the fasting condition, the pharmacokinetic parameter values of the test formulation were similar to those of the reference formulation. The 90% confidence intervals of geometric mean ratios of the test to reference formulations were 94.35–103.82% for C max , 94.79–103.26% for AUC 0– t , and 94.82–103.38% for AUC 0–∞ , which are all within the accepted bioequivalence range of 80.00–125.00%. Meanwhile, under the fed condition, the pharmacokinetic parameter values of the test formulation were also similar to those of the reference formulation. The 90% confidence intervals of geometric mean ratios of the test to reference formulations were 96.65–103.56% for C max , 98.06–103.61% for AUC 0– t , and 97.88–103.46% for AUC 0–∞ , which are all within the accepted bioequivalence range of 80.00–125.00%. The test and reference products were well tolerated, and no serious adverse events occurred during the study. Conclusions Pharmacokinetic bioequivalence of palbociclib in healthy subjects was established between the palbociclib test formulation and the reference formulation under fasting and fed conditions according to predetermined regulatory criteria. The two formulations were safe and well tolerated.